2012
DOI: 10.1111/j.1468-5876.2012.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Integration Toward an Export-Oriented Industry*

Abstract: The literature on vertical integration has constantly assumed a linear demand for the final good market. In this paper, we instead assume the demand to be a general one and use it to derive the welfare effect of vertical integration toward an export‐oriented industry. It is shown that the effect of vertical integration on the intermediate good price depends on the curvature of the derived demand curve. Moreover, vertical integration is welfare‐improving only if it increases the price of the intermediate good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Third, Tesla has reduced battery costs by expanding its production scale, such as producing batteries at a "Gigafactory" in Nevada, the United States, while also establishing a battery factory in Shanghai to meet global market demand. Finally, Tesla also uses robotics, AI, and other technologies in its production process to reduce costs and improve efficiency [4]. Now that luxury accessories are becoming more popular, Tesla also pays more attention to the construction of one-on-one service and high-quality refined products.…”
Section: Tesla's Global Salesmentioning
confidence: 99%
“…Third, Tesla has reduced battery costs by expanding its production scale, such as producing batteries at a "Gigafactory" in Nevada, the United States, while also establishing a battery factory in Shanghai to meet global market demand. Finally, Tesla also uses robotics, AI, and other technologies in its production process to reduce costs and improve efficiency [4]. Now that luxury accessories are becoming more popular, Tesla also pays more attention to the construction of one-on-one service and high-quality refined products.…”
Section: Tesla's Global Salesmentioning
confidence: 99%
“…They clearly revealed that trade policy is crucially relevant to market structure and firms 0 choices of competitive strategies. See, e.g., Neary (1994), Chang and Chen (1994), Raff and Schmitt (2005), Chen and Hwang (2012), Chang and Ryu (2015), and Wong and Liu (2016). 3 As mentioned, the retaliatory nature of anti-dumping is also granted or permitted by existing rules of the World Trade Organization.…”
Section: Orcidmentioning
confidence: 99%
“…They clearly revealed that trade policy is crucially relevant to market structure and firms′ choices of competitive strategies. See, e.g., Neary (1994), Chang and Chen (1994), Raff and Schmitt (2005), Chen and Hwang (2012), Chang and Ryu (2015), and Wong and Liu (2016).…”
mentioning
confidence: 99%